Pseudo-Tolerance and Christianophobia in Indonesia:A Case Study Analysis of Violations of Religious Freedom Against Christians from 2020 to 2025 - Sijabat, Putra Michael (Universitas Islam Negeri Raden Intan Lampung, 2026)
The cases analyzed include the violent incident in Sigi (2020), the bombing of the Makassar Cathedral (2021), the rejection of the construction of a church in Cilegon (2022), the sealing of the GKPS Purwakarta church (2023), the bullying of Catholic students at Pamulang University (2024), and the persecution of the GKSI Anugerah house of prayer in Padang (2025). This study employs a qualitative approach using a literature review and case study method. Data were collected through document analysis, including scientific articles, media reports, and publications by human rights organizations relevant to the issue of religious freedom in Indonesia. The results of the study show that violations of religious freedom do not only occur in the form of physical violence, but also through administrative restrictions and social pressure of a structural nature. This phenomenon reflects false tolerance, namely formal acceptance of diversity that is not accompanied by the protection of the substantive rights of minority groups. From the perspective of Antonio Gramsci’s theory of hegemony, this is influenced by the ideological dominance of the majority group, which legitimizes discriminatory practices. The main contribution of this study is to expand the study of religious intolerance by integrating the concepts of false tolerance and hegemony to analyze patterns of violations of freedom of religion in Indonesia across various cases. In conclusion, the role of the state in enforcing fair laws, evaluating policies on the establishment of places of worship, and strengthening multicultural education is crucial in preventing the reproduction of religious discrimination.